Industry hybrid regulation: Exploring a model for business-driven circular economy - Chapardar, Hadi (My University, 2024)
Government is often seen as the arbiter for environmental protection. Alternatively, firms can volunteer to proactively take collective action toward sustainability, called industry self-regulation. But, what happens when neither of the two alternatives can deliver the expected outcomes? This inductive study addresses such a situation in managing hazardous consumer waste in the province of Ontario, Canada, where waste management and later circular economy have been on the agenda since the 1980s. However, both self- and government regulation failed to spur the advancements required to close material loops effectively and efficiently. Finally, after three decades, actors developed a new path to transition to circular economy. This longitudinal process study focuses on this process to explore the changes in business-policy interactions that realized this transition. I analyze extensive qualitative data, including 55 interviews with top-level decision-makers in all stakeholder groups (businesses, policy-makers, NGOs, consultants, etc.). Based on the unearthed patterns, I propose a hybrid model for regulation. In this model, both business and government coordinate throughout the process to set the rules and enforce them. By allowing organically shaped competition, this model can spur proactivity and innovation, which are crucial for the transition to circular economy but are hard to incentivize in conventional policymaking. The model can be used in any situation where an urgent issue needs immediate proactive responses by business.
Keywords: circular economy; industry hybrid regulation; collective action; industry self-regulation; resource loops